Question
Multiply and simplify: \( -3 x^{2}\left(x^{3}+2 x-5\right) \)
Ask by O'Quinn Erickson. in the United States
Feb 05,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\(-3x^5 - 6x^3 + 15x^2\)
Solution
To multiply and simplify the expression \( -3 x^{2}\left(x^{3}+2 x-5\right) \), follow these steps:
1. **Distribute \(-3x^2\) to each term inside the parentheses:**
\[
-3x^2 \cdot x^3 + (-3x^2) \cdot 2x + (-3x^2) \cdot (-5)
\]
2. **Multiply each term:**
- \( -3x^2 \cdot x^3 = -3x^{2+3} = -3x^5 \)
- \( -3x^2 \cdot 2x = -6x^{2+1} = -6x^3 \)
- \( -3x^2 \cdot (-5) = 15x^2 \)
3. **Combine the results:**
\[
-3x^5 - 6x^3 + 15x^2
\]
**Final Simplified Expression:**
\[
-3x^5 - 6x^3 + 15x^2
\]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Extra Insights
First, let's distribute \( -3x^2 \) to each term inside the parentheses: \[ -3x^2 \cdot x^3 = -3x^{5} \] \[ -3x^2 \cdot 2x = -6x^{3} \] \[ -3x^2 \cdot (-5) = 15x^{2} \] Now, combine these results: \[ -3x^{5} - 6x^{3} + 15x^{2} \] Thus, the simplified expression is: \[ -3x^{5} - 6x^{3} + 15x^{2} \]